Budidaya Tanaman Kelor (Moringa Oleifera. Lam) dan Pelatihan Pembuatan Masker Daun Kelor pada Kelompok Ibu-Ibu PKK di Desa Muaro Pijoan - Haflin Haflin; Agusriani Agusriani; Halimahtussa’diyah Halimahtussa’diyah (Jurnal Abdimas Kesehatan (JAK), 2022)
The Moringa plant (moringa olifera lam), is famous because all parts of the Moringa plant have extraordinary benefits and are easy to cultivate and do not require intensive care, Moringa plants can be consumed directly or processed into various traditional medicines and products for skin care, namely Moringa leaf herbal masks. Muaro Pijoan Village is a village located on the border and its residents have a fairly large yard, some residents already plant Moringa plants, but they do not know about the benefits and how to process Moringa plants into high-value products. This service activity aims to educate 50 Family Welfare Program (FWP) women in Muaro Pijoan village, about cultivating Moringa plants and improving the skills of mothers to make herbal masks from Moringa leaves, which will be carried out in July-September 2021 with activity methods including counseling, direct practice in cultivating Moringa plants for making Moringa leaf herbal masks and packaging them into attractive products with high economic value, as well as how to market them. The results of the service activities showed an increase in the knowledge of mothers about the cultivation and utilization of Moringa plants by 38% based on the results of the pre-post test, as well as the formation of 5 groups of FWP women to cultivate Moringa plants and an increase in the skills of FWP mothers in Muaro Pijoan village by 64.0% on how to make Moringa leaf spice mask herbal products. This activity is expected to motivate mothers to cultivate Moringa plants and process them into various products for health and beauty, which have high economic value as a means of entrepreneurship, as well as the need for assistance from village officials, health workers and related agencies so that Moringa plant cultivation and manufacture This product is sustainable.